2021
DOI: 10.1002/advs.202101796
|View full text |Cite
|
Sign up to set email alerts
|

S100A9‐Targeted Cowpea Mosaic Virus as a Prophylactic and Therapeutic Immunotherapy against Metastatic Breast Cancer and Melanoma

Abstract: Prognosis and treatment of metastatic cancer continues to be one of the most difficult and challenging areas of oncology. Treatment usually consists of chemotherapeutics, which may be ineffective due to drug resistance, adverse effects, and dose‐limiting toxicity. Therefore, novel approaches such as immunotherapy have been investigated to improve patient outcomes and minimize side effects. S100A9 is a calcium‐binding protein implicated in tumor metastasis, progression, and aggressiveness that modulates the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…26 In a RAW-Blue assay, the H6 and G3 peptides were unable to elicit any immunogenic response. 26 While native CPMV can delay tumor growth, it is the targeting that imparts the added efficacy. Past ovarian cancer studies using native CPMV have demonstrated that CPMV induces the upregulation of immunostimulatory cytokines such as IFNγ and IL-6 while decreasing levels of immunosuppressive cytokines like IL-10 and TGFβ.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…26 In a RAW-Blue assay, the H6 and G3 peptides were unable to elicit any immunogenic response. 26 While native CPMV can delay tumor growth, it is the targeting that imparts the added efficacy. Past ovarian cancer studies using native CPMV have demonstrated that CPMV induces the upregulation of immunostimulatory cytokines such as IFNγ and IL-6 while decreasing levels of immunosuppressive cytokines like IL-10 and TGFβ.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Therefore, VLPs offer a unique opportunity to combine benefits of the multiple surfaces and supramolecular self-assembly of liposomes with the polyvalency and robustness of polymers, while also coming in a variety of shapes and sizes that provide a unique versatility over most other materials [41]. They are so diverse that their innate substructures have therapeutic applications for a multitude of cancer treatment such as chemotherapy, phototherapy [42], immunotherapy [43] and combinations with imaging. All these unique abilities of VLP nanoparticles to self-assemble, and for multifaceted functionalization, biocompatibility, immunogenicity, and high stability, create an ideal material for designing many therapeutic agents [27,37,40].…”
Section: Figurementioning
confidence: 99%
“…al. showed [43] the use of GGGS linker to modify their peptide of choice with thiol and azide groups for conjugation via thiol-maleimide chemistry and azide-alkyne click chemistry respectively. Poly(ethylene)glycol (PEG) linkers are popular amongst several nanocarrier platforms for providing structural stability and improving circulation half-time [73].…”
Section: Surface Modificationmentioning
confidence: 99%
“…13 In recent work, we also demonstrated that CPMV targeted to the lungs primes innate immune activation and therefore protects from the onset of lung metastasis. 14 Mechanistically, CPMV modulates the tumor microenvironment (TME) by activating the innate immune cells (switch of M2 to M1 macrophages), recruitment and activation of natural killer (NK) cells, dendritic cells (DCs), and N1 neutrophils, thereby initiating a cascade of tumor cell killing mechanisms, resulting in efficient presentation of both tumor-associated and neoantigens, and generation of a functionally active adaptive antitumor immunity via tumor antigen-specific CD4 ± and CD8 ± effector and memory T cells. 8,10 Based on this body of data, we hypothesized that intraperitoneal (IP) administration of CPMV could protect from the onset of metastatic colon tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that CPMV elicits potent systemic and durable antitumor immunity through priming the innate immune system; efficacy has been reported in mouse models of colon cancer , and other tumor models , and in canine patients . In recent work, we also demonstrated that CPMV targeted to the lungs primes innate immune activation and therefore protects from the onset of lung metastasis . Mechanistically, CPMV modulates the tumor microenvironment (TME) by activating the innate immune cells (switch of M2 to M1 macrophages), recruitment and activation of natural killer (NK) cells, dendritic cells (DCs), and N1 neutrophils, thereby initiating a cascade of tumor cell killing mechanisms, resulting in efficient presentation of both tumor-associated and neoantigens, and generation of a functionally active adaptive antitumor immunity via tumor antigen-specific CD4 ± and CD8 ± effector and memory T cells. , …”
Section: Introductionmentioning
confidence: 99%